Global equity selection strategies - Brunner R.P.; Bruner, Ross Paul. (Chicago : Glenlake Pub. ; New York : AMACOM, 1998)
"Mr. Bruner's new book, Global Equity Selection Strategies, builds on his first book, Analytical Approaches to Stock Selection, by expanding its coverage of equity products and providing a broader global orientation."--BOOK JACKET. "The book assembles a team of experts to provide sophisticated coverage of current thinking in growth, value, size, momentum, sector, and country selection strategies."--BOOK JACKET.
"The text seamlessly blends fundamental and qualitative approaches to global equity selection."--BOOK JACKET.
1. Growth-at-a-Reasonable-Price / Ross Paul Bruner -- 2. Investing in the 21st Century / Stephen R. Waite -- 3. Economic Value Added (EVA) / Vincent van Doorn -- 4. EVA as a Measure of Relative Profitability / Ross Paul Bruner -- 5. Enterprise Value/Sales Beats Price/Sales and Price/Earnings in a Three-Way Model Race / Melissa R. Brown -- 6. Normalized Value / Ross Paul Bruner -- 7. European Small-Cap Stocks: France, Germany, the Netherlands, and Switzerland / Rosemary Macedo -- 8. Interest Rates and Country Allocation Strategies / Leila Heckman and Brian Gendreau -- 9. Sector and Style Rotation: A Valuation Approach / Michael F. Wilcox and Dan Fox -- 10. Enhanced Index Portfolio Construction Using Full Covariance Optimization for a Small-Capitalization Portfolio / Bernard V. Tew -- 11. Portfolio Optimization and Emerging Markets / Theodore M. Theodore -- 12. Multifactor Equity Models / Herbert Blank.
Includes index.
Keywords: Investments, American -- Stocks -- Mathematical models; Investments, Foreign -- Stocks -- Mathematical models; Stocks -- Purchasing -- Europe -- Mathematical models; Investments, European -- Stocks; Stocks -- Purchasing -- Asia -- Mathematical models; Investments, Asian -- Stocks -- Mathematical models; Investment analysis; International finance; Stock price forecasting